The Hap Complex in Yeasts: Structure, Assembly Mode, and Gene Regulation - Mao, Yinhe; Chen, Changbin (Frontiers in Microbiology, 2019)
The CCAAT box-harboring proteins represent a family of heterotrimeric transcription factors which is highly conserved in eukaryotes. In fungi, one of the particularly important homologs of this family is the Hap complex that separates the DNA binding domain from the activation domain and imposes essential impacts on regulation of a variety of cellular functions. So far, a comprehensive summary of this complex has been described in filamentous fungi but not in the yeast. In this review, we summarize a number of studies related to the structure and assembly mode of the Hap complex in a list of representative yeasts. Furthermore, we emphasize recent advances in understanding the regulatory functions of this complex, with a special focus on its role in regulating respiration, production of reactive oxygen species (ROS) and iron homeostasis.